When Inquiry Isn’t Enough: Why Structured Reflection Can Strengthen Preservice Science Teachers’ Critical Thinking - Verawati, Ni Nyoman Sri Putu; Wahyudi, Wahyudi; Nisrina, Nina (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Inquiry-based learning is frequently treated as a ready-made route to critical thinking, but classroom inquiry often becomes procedural unless students are pushed to examine assumptions, justify claims, and revise interpretations. This commentary discusses the focal study “Emphasizing reflective processes in scientific inquiry and its impact on preservice science teachers’ critical thinking skills” and argues that its strongest contribution is showing how structured reflective elements can turn inquiry activities into repeated practice in reasoning. At the same time, the evidence should be read carefully: the gains are very large, and the intervention bundles several supports (anomalies, monitoring worksheets, prompts, and feedback) that may each contribute. We outline alternative explanations, identify what the study clarifies and what it does not yet prove, and offer implications for future research designs and teacher-education practice.